2021
DOI: 10.5334/jbsr.2592
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Arachnoid Web: A Rare Cause of Myelopathy

Abstract: Teaching point: The scalpel sign is pathognomonic for a dorsal arachnoid web, a rare clinical-radiologic entity that can cause myelopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…1,29 In T2-weighted constructive interference in steady state sequences or true FISP, it might be possible to visualize the web. 4,5,23 In our series, it was possible to visualize the SAW in T2 true FISP MRI. Chang et al 6 concluded that localizing the location of CSF blockage precisely limits the extent of resection.…”
Section: Radiological Diagnosis and Radiological Fumentioning
confidence: 71%
See 2 more Smart Citations
“…1,29 In T2-weighted constructive interference in steady state sequences or true FISP, it might be possible to visualize the web. 4,5,23 In our series, it was possible to visualize the SAW in T2 true FISP MRI. Chang et al 6 concluded that localizing the location of CSF blockage precisely limits the extent of resection.…”
Section: Radiological Diagnosis and Radiological Fumentioning
confidence: 71%
“…Hamilton et al 11 and Buttiens et al 5 concluded that is the gold standard for diagnosing SAW with the pathognomonic so-called "scalpel sign" (or scalpel blade sign) 21 because of the resemblance of the silhouette of a surgical scalpel blade. 11 However, it might be di cult for MRI to visualize focal arachnoid lesions.…”
Section: Radiological Diagnosis and Radiological Fumentioning
confidence: 99%
See 1 more Smart Citation
“…Despite increasing research in recent years, the etiology of SAW is still unclear. Some researchers posit that webs form from disrupted arachnoid cyst formation, from the rupture of an arachnoid cyst, 13 , 14 or as a sequela of spinal trauma or surgery. Similar to Nisson et al., 6 we found a low prevalence of previous spinal surgery or trauma among our sample, indicating that additional research into the causes of SAW is warranted.…”
Section: Discussionmentioning
confidence: 99%
“… 6 Multiple studies have further suggested that SAW is underdiagnosed and underreported, perhaps due to slow symptom progression as described in our sample (mean symptom duration >3 years) or to the potential for asymptomatic presentation. 13 The heterogeneity of symptoms experienced by patients with SAW may also complicate diagnosis. Patients in our sample presented with various combinations of symptoms ranging from pain to incontinence and gait disturbance.…”
Section: Discussionmentioning
confidence: 99%